Pendidikan Karakter Melalui Pelatihan Karawitan di Sanggar Cipto Laras - Mega Rully Oktavia; Atip Nurharini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The low interest of teenagers as successors of traditional culture and the increasingly fading character values is the background of this research. The researcher sees the need for concrete actions to improve the character of today's youth by implementing character education. Character education itself is an effort to help individuals cultivate attitudes, thoughts, feelings, words, and actions that align with the values of norms, customs, and the culture of the nation. Character education is not only limited to formal institutions but must also be comprehensive through both non-formal and informal institutions. The implementation of character education in the gamelan studio is a means that can be used to instill character values. This research aims to describe the role of the coach in the implementation of character education and to describe the character values contained in the implementation of gamelan training at Sanggar Cipto Laras. This research employs a qualitative case study approach using data collection techniques of observation, interviews, and documentation. Data analysis utilizes the Miles and Huberman model by performing data reduction, data presentation, conclusion drawing, and verification. The results of this study are: 1) The role of trainers in the implementation of character education includes being a role model, inspirator, motivator, dynamizer, and evaluator. 2) The values contained in the art training include creativity, discipline, love for the homeland, friendship, responsibility, environmental awareness, and hard work. Thus, the role of a trainer is crucial in efforts to cultivate character for the next generation of morally and ethically valuable citizens. The success of character education implementation requires consistency and collective awareness so that these values can be well internalized within each individual.